PENGEMBANGAN MEDIA PAPAN HURUF MENGGUNAKAN METODE SCRAMBLE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS II SDN 105320 KUTA JURUNG - Epriyani Br Perangin-Angin; Sujarwo Sujarwo (STKIP Subang, 2024)
This research is a type of research and development with reference to the 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data was a questionnaire. The data analysis technique is descriptive qualitative. This research produced a product in the form of a letter board to improve reading skills which was declared suitable for use in class II elementary school. This can be seen based on the results of validation by material experts, media experts and teacher responses. The results of material validation show that the overall assessment of material experts regarding media obtained a percentage of 92%. This percentage includes very valid criteria (very feasible) to be used as a medium to improve the reading skills of second grade elementary school students. The media validation results showed that the overall assessment average was 94%. This percentage includes very valid criteria (very feasible) for improving the reading skills of second grade elementary school students. The practicality and effectiveness of learning media is proven by the accuracy of pronunciation, intonation, fluency, clarity of voice, and complete reading of students when reading the tale of the deer and the badung lizard in front of the class. Validation of reading skills can be seen from the teacher's assessment of getting a score of 96% from 5 statements.